Thinking Critically and Critical Thinking: Integrating Online Tools to Promote Critical Thinking - B. Jean Mandernach (Park University, 2006)
The value and importance of critical thinking is clearly established; the challenge for instructors lies in successfully promoting students' critical thinking skills within the confines of a traditional classroom experience. Since instructors are faced with limited student contact time to meet their instructional objectives and facilitate learning, they are often forced to make instructional decisions between content coverage, depth of understanding, and critical analysis of course material. To address this dilemma, it is essential to integrate instructional strategies and techniques that can efficiently and effectively maximize student learning and critical thinking. Modern advances in educational technology have produced a range of online tools to assist instructors in meeting this instructional goal. This review will examine the theoretical foundations of critical thinking in higher education, discuss empirically-based strategies for integrating online instructional supplements to enhance critical thinking, offer techniques for expanding instructional opportunities outside the limitations of traditional class time, and provide practical suggestions for the innovative use of critical thinking strategies via online resources.